The Fractured Self in Contemporary Saudi Poetry: Selected Models - Al-Atrash, AlHanoof Bint Sulaiman Bin Mohammed (Arts for Linguistic & Literary Studies, 2025)
This study investigates the fractured self in contemporary Saudi poetry through selected examples. It conceptualizes self-fracture as a critical mode of poetic self-expression, reflecting a state where the self is caught between reality and aspiration, or between power and vulnerability—physically, emotionally, or imaginatively. Rather than treating self-fracture merely as a thematic concern, the study frames it as an interpretive key that reveals aesthetic dimensions, experiential depth, and poetic vision. The research focuses on three primary manifestations: spiritual fracture, fracture in the face of loss, and fracture in the quest for meaning. These forms are analyzed not just for their content but also for their impact on shaping poetic identity and consciousness. The study concludes that expressions of brokenness, regardless of form or intensity, function as a tool through which poets engage with self-awareness, relational dynamics, and existential reflection. In contrast to inflated expressions of ego, the articulation of fracture often unveils deeper truths about the self and its place in the world.